Acyclovir in first attacks of genital herpes and prevention of recurrences. Issue 1 (February 1986) - Mindel, A; Weller, I V; Faherty, A; Sutherland, S; Fiddian, A P; Adler, M W
Abstract : Sixty women patients experiencing a first attack of genital herpes were randomly treated with either oral acyclovir for 42 days or oral acyclovir for five days followed by placebo for 37 days. The median time to the first recurrence in patients receiving acyclovir for 42 days was 66.5 days compared with 24 days in those who received acyclovir for only five days (p less than 0.0001). This significant difference, however, was only observed for the treatment period. The frequency of recurrences was also reduced during the period of treatment in those who received prolonged treatment. During the subsequent follow up period, however, patients in both groups had a similar frequency of recurrences. Patients with infections due to herpes simplex virus type I (HSV I) had a significantly longer time to the first recurrence (p less than 0.001) and fewer recurrences (p less than 0.001) than those infected with HSV II, irrespective of treatment.